Energy, exergy, environmental and economic analysis of industrial fired heaters based on heat recovery and preheating techniques - Shekarchian, M.; Zarifi, F.; Moghavvemi, Mahmoud; Motasemi, F.; Mahlia, T.M.I. (Elsevier, 2013)
Fired heaters are ubiquitous in both the petroleum and petrochemical industries, due to it being vital in their day to day operations. They form major components in petroleum refineries, petrochemical facilities, and processing units. This study was commissioned in order to analyze the economic benefits of incorporating both heat recovery and air preheating methods into the existing fired heater units. Four fired heater units were analyzed from the energy and environmental point of views. Moreover, the second law efficiency and the rate of irreversibility were also analyzed via the exergy analysis. Both analyses was indicative of the fact that the heat recovery process enhances both the first and second law efficiencies while simultaneously assisting in the production of high and low pressure water steam. The implementation and usage of the process improves the thermal and exergy efficiencies from 63.4% to 71.7% and 49.4%, to 54.8%, respectively. Additionally, the heat recovery and air preheating methods leads to a substantial reduction in fuel consumption, in the realm of up to 7.4%, while also simultaneously decreasing heat loss and the irreversibility of the unit. Nevertheless, the results of the economic analysis posits that although utilizing an air preheater unit enhances the thermal performance of the system, due to the air preheater's capital and maintenance costs, incorporating an air preheater unit to an existing fired heater is not economically justifiable. Furthermore, the results of the sensitivity analysis and payback period showed that the economic results are highly susceptible to the interest rate, and the payback period for the most economical case is 2.6 years.